Internationalization capacitation of a SME in the dental prosthetics industry: Oralook - Gaspar, Sylvain (2018)
The phenomenon of market globalization has been posing new challenges and opportunities for Portuguese companies, resulting in internationalization initiatives. With the opening and expansion of markets and with the increasing competition and pace of innovation, companies seek for growth in international markets. Increasingly, companies’ must be able to respond to challenges that threaten their economic survival, resulting in stagnation. Internationalization is one of business strategic responses to the globalization challenge. The aim of this dissertation is to develop an in-company project to evaluate a dental laboratory internationalization capacity, and the subject to be studied is a top technological company, Oralook. The motivation to internationalize emerged from an entrepreneurial vision of the company’s managing partner, Gonçalo Duque, a dental prosthetics expert. Today, Oralook has one of the best facilities among Portuguese dental laboratories, equipped with the latest dental technology worldwide, which allows the sale of products and services outside the domestic market. From the detailed internal and external analysis, it is possible to answer pertinent questions brought up by careful research and find solutions towards shaping the future of the laboratory’s internationalization process.